Taking care of the elderly with alzheimer's: feelings and experience revealed by their caregivers - Almeida, Lídia Gonçalves Rabelo de Souza (2014)
Aim: to learn the perception of the caregiver in relation to the experience of taking care of the elderly with dementia of the Alzheimer type. Methods: qualitative study, with a sample of eight caregivers of patients with Alzheimer's disease in a city of Minas Gerais. Interviews were conducted with a semistructured script, from December 2012 to February 2013. The material was analyzed using the content analysis technique.Results: the following categories were identified: the disease in the caregiver’s perspective, and living with the limitations of both patient and caregiver. Conclusions: the need for continuous care makes caregiver assistance indispensable and, as the disease progresses, the caregiver assumes the patient’s activities of daily living. Therefore, support as well as education and information about the disease are needed.